The relationship between body image perception and eating pattern - Rahmanu, Irfan; Eliska, Eliska; Harahap, Reni Agustina (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: Perception of body image and eating patterns in adolescents are two very important aspects of their health in their development. Body image reflects an individual's view of their physical appearance, while eating patterns refer to daily food consumption habits that can affect overall health. Adolescents, especially female students in high school (SMA), often experience pressure to meet beauty standards set by social media, peers, and other factors. Eating patterns are the most important behavior that can affect nutritional status. This is because the quantity and quality of food and beverages consumed will affect nutrient intake, thereby affecting individual and community health.Objectives: The aim of this study is to determine the relationship between body image perception and eating patterns among female students of Kesuma Bangsa Londut High School (SMAS).Methods: This study used a descriptive correlational design with a cross-sectional approach. Data collection was done using a Body Image questionnaire based on the Multidimensional Body Self-Relations Questionnaire-Appearance Scale (MBSRQ-AS) theory and a Food Frequency Questionnaire for eating patterns.Results: The statistical test results showed that the obtained p-value was 0.001 <0.05, indicating that H0 was accepted and Ha was rejected, meaning there is a relationship between body image and eating patterns among female students at SMAS Kesuma Bangsa Londut.Conclusion: The majority of teenage girls at SMAS Kesuma Bangsa Londut are 16 years old with negative body image, manifested in the desire to have an ideal body, while eating patterns tend to be poor with certain food consumption more than once a day such as chicken meatballs. A significant relationship was found between body image and eating patterns, where teenage girls with negative body image tend to have poor eating patterns and vice versa.